Elemental Abundances in M31: Individual and Coadded Spectroscopic [Fe/H] and [α/Fe] throughout the M31 Halo with SPLASH - J. Leigh Wojno; Karoline M. Gilbert; Evan N. Kirby; Ivanna Escala; Puragra Guhathakurta; Rachael L. Beaton; Jason Kalirai; Masashi Chiba; Steven R. Majewski (The Astrophysical Journal, 2023)
We present spectroscopic chemical abundances of red giant branch stars in Andromeda (M31), using medium-resolution ( R ∼ 6000) spectra obtained via the Spectroscopic and Photometric Landscape of Andromeda’s Stellar Halo survey. In addition to individual chemical abundances, we coadd low signal-to-noise ratio spectra of stars to obtain a high enough signal to measure average [Fe/H] and [ α /Fe] abundances. We obtain individual and coadded measurements for [Fe/H] and [ α /Fe] for M31 halo stars, covering a range of 9–180 kpc in projected radius from the center of M31. With these measurements, we greatly increase the number of outer halo ( R _proj > 50 kpc) M31 stars with spectroscopic [Fe/H] and [ α /Fe], adding abundance measurements for 45 individual stars and 33 coadds from a pool of an additional 174 stars. We measure the spectroscopic metallicity ([Fe/H]) gradient, finding a negative radial gradient of −0.0084 ± 0.0008 for all stars in the halo, consistent with gradient measurements obtained using photometric metallicities. Using the first measurements of [ α /Fe] for M31 halo stars covering a large range of projected radii, we find a positive gradient (+0.0027 ± 0.0005) in [ α /Fe] as a function of projected radius. We also explore the distribution in [Fe/H]–[ α /Fe] space as a function of projected radius for both individual and coadded measurements in the smooth halo, and compare these measurements to those stars potentially associated with substructure. These spectroscopic abundance distributions add to existing evidence that M31 has had an appreciably different formation and merger history compared to our own Galaxy.